PERFORMANCE EVALUATION DECISION SUPPORT SYSTEM USING THE LECTURER ANALITYCAL HIERARCHY PROCESS (CASE STUDY: STMIK DHARMA WACANA METRO) - Nurdiyanto, Heri; Vem, Envermy (244-5567)
To be continued competitive with competitors, STMIK Dharma Wacana continues to improve the quality. One of the efforts is to improve the quality of faculty performance, by assessing a lecturer for the Tri Dharma University and Personality. Referring to the faculty priorities, STMIK Dharma Wacana assessing academic performance of faculty of year by using Key Performance Indicators to determine a lecturer with the best quality and ability that will ultimately affect the determination of the faculty with the best performance. Constraints faced is the lack of information systems that can specifically provide support for decision-makers, namely the Chairman STMIK Dharma Wacana and management, making it difficult generate optimal decision. For data analysis, this study using descriptive analysis techniques and instruments used to determine policy priorities, namely Analytic Hierarchy Process (AHP), and in this study proposed a decision support information system or Decision Support System (DSS). The results of data processing in mind that the criteria Tridarma Higher Education and Personality. Affecting the determination of the performance of lecturers teaching each year. The results are then simulated through a hierarchical method. Of the hierarchy then made a decision support system in terms of determining the lecturer with the best performance that will teach certain subjects in each teaching. Â Keywords: Key Performance Indicators, Analytic Hierarchy Process, Decision Support Systems, Lecturer performance.